Teaching teachers: Challenges and Perspectives - Saleh, I.; Khine, Myint Swe (Nova Science Publishers, Inc., 2011)
Teacher education has long been criticized as a weak intervention in the life of a teacher, barely able to make a dent in the idea and behaviors teachers bring with them into classroom from their own days as students" (Darling-Hammond, 2006, P.6). Teacher education, however, plays a vital role in educating our future teacher-which in turn educates our children in today's information age and knowledge-based economy. Simply having knowledge is not enough; students having the necessary skills to apply knowledge in real life are more important. If any nation is in the process of improving education, it is imperative that the nation look closely at how it organizes its teacher education program. Several studies have confirmed that teachers make a difference in students' learning more than any other factors in schools (Sanders and Horn, 1994; Sanders and Rivers, 1996; Wright, Horn, and Sanders, 1997).In the United States, the need to raise the quantity and quality of the teaching force is imperative. According to Alliance for Excellent Education, "Teacher Attrition: A Costly Loss to the Nation," Issue Brief, (Washington, DC: Alliance for Excellent Education, August, 2005), the United States is facing nearly 200,000 teacher vacancies a year. According to the study, this is due to attrition rates among new teachers, the retirement of baby boomer teachers, increases in student numbers due to immigration, population redistribution, and regional growth.